PERUBAHAN BENTUK PERTUNJUKAN TARI NYAMBAI DI LAMPUNG BARAT - Fitri Daryanti (Pascasarjana Institut Seni Indonesia Surakarta, 2010)
The Nyambai Dance is one of cultural components of Lampung local society which exists in the meeting of single men and women which is held as a part of the traditional wedding ceremony. It develops gradually to be a tourism performing art and the change are represented on the form of performing art. The purpose of this research was to describe the change of form of Nyambai Dance and the causal factors. The research used qualitative method through ethno-choreology approach. The approach was done by textual and contextual analyses. The textual analysis was looked at the structure of dance, while the contextual analysis was from the function of Nyambai Dance and the causal factors of the change. The analysis of change of form used the theoretical structure of Marco De Marinis and Soedarsono which stated that it had to know the elements of performance in order to describe the change of form of the performing art. The elements were actor, movement, the pattern of floor, music, make-up and costume, property, and the other supporting elements. The researcher used the concept of Alvin Boskoff in order to analyze the causal change. The concept stated that the change which happened can be seen from the internal and external factors.The result of the research shows that there are the changes of form of Nyambai Dance in several elements, they are: the adding and making of movement, the pattern of floor, music, make up and costume, and property. The change also happens in the place and time of performance, meanwhile the causal factors of the change was affected by several factors, and they are: economics, education, technology, and transition of cultural value. The change of form of Nyambai Dance is a participation of the local society, artists, and The Local Department of Culture and Tourism through tourism promotion program, so that Nyambai Dance as one of the tourism assets in art in Lampung Barat. Keywords: Nyambai Dance, wedding ceremony, tourism.